Generative AI Use by Capital Market Information Intermediaries: Evidence from Seeking Alpha - Bradshaw, Mark T.; Ma, Chenyang; Yost, Benjamin P.; Zou, Yuan (Journal of Accounting Research, 2026)
ABSTRACT We study the use of generative AI for firm‐specific financial analysis on the Seeking Alpha platform. After the initial launch of ChatGPT in November 2022, the share of AI‐generated articles rose sharply to 13.5% of all articles, then declined in late 2023 after Seeking Alpha equated the use of AI to plagiarism and announced a prohibition on its use. We organize our study around two questions: (1) Does AI use increase author productivity? and (2) does AI use have capital market consequences and ultimately affect the informational landscape? We find that authors who adopt AI become more productive, publishing more articles and covering more new firms than non‐adopters. Findings on AI article informativeness are more nuanced. On average, AI articles are less informative than human‐written articles, eliciting smaller trading volume and abnormal return responses. However, AI use leads to increased firm coverage and in turn to improved liquidity and faster price discovery. Our findings suggest that, while AI‐generated articles are currently perceived as less informative than human‐written articles, their comparatively low cost enables increased firm coverage and thereby improves the overall informational landscape.